STUDI KASUS: KONSUMSI SAYUR BENING KELOR DALAM ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN ANEMIA SEDANG - Fauziah, Arvicha; Jambormias, Jacob L (Poltekkes Kemenkes Maluku, 2024)
According to WHO, the prevalence of pregnant women suffering from anemia in 2012 reached 41.8% in the world and Asia was ranked second in the world after Africa with a prevalence of anemia during pregnancy reaching 48.2%. The prevalence of iron deficiency anemia in pregnant women in Indonesia is 24.5% in 2021. The aim of this case study is to determine the outcome of midwifery care for pregnant women who suffer from anemia through the consumption of the clear moringa plant. The case study was conducted at Pustu Arui Das Lorulun Community Health Center. The method used is a case study approach in which pregnant women with anemia conduct home visits. The results of midwifery care showed that after pregnant women consumed the clear vegetable Moringa, hemoglobin levels increased from 7 gr/dl to 9 gr/dl for 8 days. The conclusion is that providing pregnant women with the clear vegetable Moringa can increase hemoglobin levels in midwifery care. Keywords: Moringa oleifera, Pregnant, Anemia.